ISSUES OF COVERAGE OF THE HISTORY OF THE LOWER SIRDARYA REGIONS IN SOURCES (TAMADDUN NURI JURNALI, 2025)
The article analyzes the primary written and material sources that provide information about the Lower Syrdarya region, its socio-economic life and the ancient population that lived in the region. The study first examines the primary written sources on the history of the region and then the results of archaeological research conducted in the 20th century.